(untitled) (Fiep Bulletin - online, 2014)
Anthropometric and motric potential structure is dynamic, requiring careful research to determine its components and characteristics. After conducting this study there has been found the real motric potential and anthropometric profile of high school students, and could thus establish a work program to eliminate gaps of somatic development and improve motric indicators. Suceava County has 5 municipalities, 11 towns and 98 communes and a population of 614,451. In Suceava County there are 37 high schools with more than 20000 pupils. Our study was made in 7 high schools (from the urban and rural areas) during school year 2011/2012. At the study there were more than 2100 participants. Identifying anthropometric and motric profile of high school student would help to optimize the Physical Education Curricula at this level and to adapt it to motric potential and somatic development level of today’s students. The main goal is to shape the anthropometric and motric profile of the high school pupils. Somatic index values are within the limits of previous studies, but there is a noticeable increase in weight, going to maximum values while the height is average values. For the results of motric tests, the data showed low values indicating low performance, mostly contained within grades 5-8. This research has shown that it is essential that the objectives of physical education teaching in high school should be tailored to students’ motric potential, which according to our study is in decline and a tendency toward overweight pupils (BMI – from 19-20 to 21 points). The limited aspect of the study is the fact it was performed locally when most data from previous studies are conducted at national level, in our case the number of subjects being 2128.